Mechanical properties of woven jute–glass hybrid-reinforced epoxy composite. (December 2014) - Gujjala, Raghavendra; Ojha, Shakuntala; Acharya, SK; Pal, SK
As major historical periods such as Stone Age, Bronze Age, and Iron Age, the development of new materials was the fundamental to all the periods. In the present investigation, a new hybrid composite with epoxy as a resin and reinforcing both biowaste (jute) and traditional fiber (glass) as continues layered mat composites and also study experimentally the effect of the stacking sequence on tensile, flexural, and interlaminar shear properties. Composites were prepared by using hand lay-up technique. All the laminates were prepared with a total of four piles, by varying the position of glass and jute. One group of all jute and glass laminate was also fabricated for comparison purpose. Specimen preparation and testing were carried out as per ASTM standards. Tests were conducted on INSTRON H10KS Material Test System at room temperature using automatic data acquisition software. The results indicated that the jute fiber and hybrid composite give encouraging results when compared with the neat epoxy. The morphologies of the composites are also studied by scanning electron microscope.